تأثر شعراء نصارى العرب بمبادئ الإسلام وأفكاره - Mukhlef, Ahmad Hamid (Afkar: Jurnal Akidah dan Pemikiran Islam, 2011)
This study investigates the impact of Islamic thought on the modern Arab Christian literature by analyzing the poetics works of the Christian Arab. The research concluded that a large number of Christian writers and poets (twenty-three man of letters and poet) have been influenced by Islamic thought. They discuss issues on Islam and were in the first row to defend Islam and Islamic thought. The research demonstrates that, in a way, they are honest in their saying and perception.